2017
DOI: 10.1038/s41598-017-10902-0
|View full text |Cite
|
Sign up to set email alerts
|

YeeJ is an inverse autotransporter from Escherichia coli that binds to peptidoglycan and promotes biofilm formation

Abstract: Escherichia coli is a commensal or pathogenic bacterium that can survive in diverse environments. Adhesion to surfaces is essential for E. coli colonization, and thus it is important to understand the molecular mechanisms that promote this process in different niches. Autotransporter proteins are a class of cell-surface factor used by E. coli for adherence. Here we characterized the regulation and function of YeeJ, a poorly studied but widespread representative from an emerging class of autotransporter protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 90 publications
1
29
0
Order By: Relevance
“…To assess the functionality of UpaE in isolation, we utilized a plasmid based overexpression system it the E. coli K-12 background strain MS427 (48). MS427 has a mutation in the Ag43-encoding flu gene rendering it unable to facilitate biofilm formation or self-aggregation, and has previously been used successfully to probe the function of other autotransporters (20, 4853). Immunoblots of whole cell lysates generated from MS427 transformed with a UpaE expression plasmid using a polyclonal anti-serum raised to a UpaE-MBP fusion protein showed a band consistent with the 271kDa predicted molecular weight of UpaE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the functionality of UpaE in isolation, we utilized a plasmid based overexpression system it the E. coli K-12 background strain MS427 (48). MS427 has a mutation in the Ag43-encoding flu gene rendering it unable to facilitate biofilm formation or self-aggregation, and has previously been used successfully to probe the function of other autotransporters (20, 4853). Immunoblots of whole cell lysates generated from MS427 transformed with a UpaE expression plasmid using a polyclonal anti-serum raised to a UpaE-MBP fusion protein showed a band consistent with the 271kDa predicted molecular weight of UpaE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluoresence microscopy was performed essentially as previously described (53). Overnight cultures supplemented with the appropriate antibiotics and 1mM of IPTG were fixed to an OD 600 of 0.4, spotted onto a glass slide and allowed to dry.…”
Section: Methodsmentioning
confidence: 99%
“…A similar structure was recently described for Y. enterocolitica (Lenchenko et al ., 2019). Many IATs from other organisms, particularly E. coli and the fish pathogen E. tarda , have been implicated in biofilm formation (Nesta et al ., 2012; Dong et al ., 2013; Martinez‐Gil et al ., 2017; Goh et al ., 2019). Therefore, we also investigated the role of the two Y. ruckeri IATs in our biofilm model.…”
Section: Discussionmentioning
confidence: 99%
“…YeeJ is a very large protein (2358 amino acids). Overexpression of YeeJ in E. coli MG1655 significantly increased the biofilm formation compared to the WT E. coli MG1655 strain (Nesta et al ., 2012; Martinez‐Gil et al ., 2017). Bioinformatics analysis showed that YeeJ, like other IATs, contains a LysM domain, which binds to peptidoglycan and stabilizes the proteins as shown previously for another E. coli IAT, Intimin (Leo et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation